Study on the Demand and Influencing Factors of Vocational Skill Training for Industrial Workers in the Era of “Machine Replacement” - Ke, Lele; Liu, Kai (Innovative Applications of AI, 2025)
Under the current background of globalization and technological innovation, “Machine Replacement” has become an irreversible trend in many industries, which not only reshapes the demand structure of the labor market, but also poses new challenges to the career and skill requirements of laborers, especially industrial workers, and urgently needs to continuously promote the updating and development of industrial workers’ skills. Based on a questionnaire survey of 281 industrial workers, this study found that age, gender, industry, and whether or not they are in the place of domicile affect industrial workers’ demand for vocational skills training, and constructed a model of moderated mediating effects between industrial workers’ self-efficacy, information acquisition ability, and occupational ambiguity and their willingness to be trained in skills. As a result, local governments should promote the optimal allocation of production factors and social resources for skills training, Enterprises should play a major role in vocational skills training, and vocational colleges should play a public service role in labor force skills development.